2022
DOI: 10.1111/pan.14566
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental intraoperative crystalloids for pediatric postoperative nausea and vomiting—A systematic review and meta‐analysis

Abstract: Background Postoperative nausea and/or vomiting is a relatively frequent occurrence after general anesthesia in pediatric patients. Supplemental perioperative crystalloid fluid administration has been shown to have a positive effect on the incidence of nausea and/or vomiting in adults undergoing surgery. The question arises whether supplemental intraoperative intravenous fluids in pediatric patients offers beneficial results with regards to pediatric postoperative nausea and/or vomiting. Methods Pubmed, EMBASE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Operative time is related to number of fusion levels or curve complexity, and evaluating its outcomes in current literature is challenging because of lack of a reporting standards in PSF surgery 56 . The role of intraoperative and postoperative blood loss and volume status on PONV rates is also in need of focused investigation 57-62 . In this review, intraoperative interventions such as dexamethasone and ketamine showed some reduction in PONV, however, lacked consistent findings to support their use 9,35-39 .…”
Section: Discussionmentioning
confidence: 99%
“…Operative time is related to number of fusion levels or curve complexity, and evaluating its outcomes in current literature is challenging because of lack of a reporting standards in PSF surgery 56 . The role of intraoperative and postoperative blood loss and volume status on PONV rates is also in need of focused investigation 57-62 . In this review, intraoperative interventions such as dexamethasone and ketamine showed some reduction in PONV, however, lacked consistent findings to support their use 9,35-39 .…”
Section: Discussionmentioning
confidence: 99%
“…This study has limitations as follows: first, although this was a prospective study with data of the primary outcome from investigator follow-up, there were still some outcome data from anesthesia record sheets and electronic medical systems; therefore, confounding factors could not be effectively eliminated. Studies have revealed a negative correlation between intraoperative crystal infusion volume and the occurrence of PONV [ 16 ]. For laparoscopic cholecystectomy surgery, the incidence of PONV is lower at a high intraoperative crystal infusion rate (≥2 mL/kg/h) than at a lower infusion rate (<2 mL/kg/h) [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, fluid therapy instead of fasting can also be formulated as 2cc/kgBW/hour of fasting (Gan et al 2019). According to Puri, Bandyopadhyay, and Ashok (2023), the daily fluid requirement can be determined using the Holiday Fresh formula, which replaces fluid lost through urine formation, gastrointestinal secretions, sweat, and expulsion of fluid through the lungs, also known as insensible losses.…”
Section: Discussionmentioning
confidence: 99%